Symbiotic Associations: Key Factors That Determine Physiology and Lipid Accumulation in Oleaginous Microorganisms - Deka, Deepi; Sonowal, Shashanka; Chikkaputtaiah, Channakeshavaiah; Velmurugan, Natarajan (Frontiers in Microbiology, 2020)
Symbiosis naturally provides an opportunity for microorganisms to live together by mutual or one-way benefit. In symbiotic relationships, the microorganisms usually overcome the limitations of being a free-living. Understanding the symbiotic relationships of oleaginous microorganisms provides potential route for the sustainable production of microbial-based alternative fuels. So far, several studies have been conducted in oleaginous microorganisms for the production of alternative fuels. However, major draw-backs of oleaginous microorganisms’ including requirement of high-quantity of nutrient sources, average lipid productivity, and requirements of energy and chemicals for harvest and separation of lipid bodies, make them more expensive. Oleaginous symbiotic microorganisms can successfully be applied to answer the problems of individual oleaginous species. Of symbiotic associations, lichens and selective species of oleaginous endosymbiotic mucoromycotina have received substantial interest as better models to study the evolutionary relationships as well as single cell oil production. Construction of artificial lichen system composed of cyanobacteria and oleaginous yeast has been achieved for sustainable production of lipids with minimum energy demand. Recently, endosymbiotic mucoromycotina species have been recognized as potential sources for biofuels. Studies found that endohyphal bacterium influences lipid profiling in endosymbiotic mucoromycotina species. Studies on the genetic factors related to oleaginous characteristics of endosymybiotic mucoromycotina species are scarce. In this regard, this review summarizes the different forms of symbiotic associations of oleaginous microorganisms, and how symbiotic relationships are impacting the lipid formation in microorganisms. Further, the review also highlight the importance of evolutionary relationships and benefits of co-culturing (artificial symbiosis) approaches for sustainable production of biofuels.